The vertebrate corneal epithelium: From early specification to constant renewal. Issue 10 (30th August 2014) - Dhouailly, Danielle; Pearton, David J.; Michon, Frederic; Mansour, Suzanne L.; Ornitz, David M.
<x xml:space="preserve">Abstract</x> BACKGROUND: The cornea is an ectodermal/neural crest derivative formed through a cascade of molecular mechanisms to give rise to the specific optical features necessary for its refractory function. Moreover, during cornea formation and maturation, epithelial stem cells are sequestered to ensure a constant source for renewal in the adult. RESULTS: Recent progress in the molecular and stem cell biology of corneal morphogenesis and renewal shows that it can serves as a paradigm for epithelial /mesenchymal organ biology. This review will synthesize historical knowledge together with recent data to present a consistent overview of cornea specification, formation, maturation, and maintenance. CONCLUSIONS: This should be of interest not only to developmental biologists but also ophthalmologists, as several human vision problems are known to be rooted in defects in corneal development. Developmental Dynamics 243:1226–1241, 2014. © 2014 Wiley Periodicals, Inc.